Profesionalitas Guru dalam Meningkatkan Prestasi Belajar Siswa (Study Kasus di Pondok Pesantren Ash-Shidiqiyah) - Bastomi Bastomi; Muhammad Win Afgani; Afriantoni Afriantoni (Departement of Mathematics Education, 2024)
Realizing that teachers are one of the keys to educational success, various efforts have been made to develop the competence and performance of professional teachers to improve the quality of teachers through understanding that teachers who can carry out their duties professionally and have a commitment to carrying out their duties and functions as teachers to the maximum can play a very important role. in increasing student learning achievement. The results of this research state the teacher's ability to compose learning tools, the ability to improvise learning methods and strategies and the ability to assess student learning outcomes through class-based assessments, while professional abilities; described as the ability to master a field of study seen from the educational background of teachers who have academic qualifications and teachers who teach according to their expertise and major, the ability to understand students, the ability to master educational learning through the ability to understand types of subjects, organize subject matter and utilize learning resources.